Opportunities for the development of medical education with the use of technologies. Lessons from the pandemic (Revista Innova Educación, 2022)
The objective was to describe the conditions in which the classes were held once the confinement for non-essential activities was declared. A descriptive, cross-sectional methodology was used with a hermeneutic approach. A questionnaire was applied to a sample of 357 members of the Health Sciences student body of the Universidad Juárez Autónoma de Tabasco, Mexico, in May 2020. Semi-structured interviews were also conducted. In the results, it was identified that the student body had an Internet connection (87.1%), smartphones (82.5%), and a laptop (75.8%). The student body's activities were elaborating slides for presentations in class (78.8%) and reading in their textbooks (67.5%). The activities of the teaching staff were to comment at the end of the presentations (58.9%), and they requested the search for information for the elaboration of texts (61.8%). The student body mentioned that their stress levels increased (52.7%), and the tasks became more challenging to do (45.2%). The migration to virtual environments was not accompanied by changes in the structure of school activities, so it is most likely that when returning to face-to-face learning, the traditional class will be maintained.
Keywords: virtual classroom; confinement; project development; learning management system